Pemikiran Pendidikan Ibn ‘Arabi dan Relevansinya dalam Pendidikan Islam Kontemporer - Mukit, Abdul (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2019)
This article attempts to analyze the education thinking of the great tasawuf character, muhyiddin Ibn 'Arabi and relevance as one of the solutions in the world of contemporary islamic education. Through the methodology of the library research, there will be in-depth and detailed examination of ibn 'arabi's educational thoughts from several of his works. Ibn 'arabi's thoughts are like human concepts, concepts of science, teachers (syeikh) concepts will be described in such a way as obtaining a foothold in the full description of the object. The purpose of education according to ibn 'arabi, which basically means to be perfect human (insan kamil) will be the core for digging the program, process, curriculum and evaluation. To support all of this formula needs educated and talented teachers who have high soul against the intended destination, so that the perfect human will be created , a humen who is entitled and proud as the khalifah Allah